Emerging Technologies and Sustainability Integration in Industry 4.0 Manufacturing: A Bibliometric Analysis - Arya Sena; Latief Syahdika; Rafli Ramadhan; Rafli Aulia (Universitas Islam Malang, 2026)
The advancement of Industry 4.0 technologies has accelerated the transformation of manufacturing systems toward intelligent, interconnected, and sustainability-oriented industrial environments. Although numerous studies have explored smart manufacturing and digital transformation, limited bibliometric research has comprehensively examined the integration of intelligent manufacturing technologies with sustainability-driven production systems in the post-pandemic industrial era. This study aims to analyze the scientific development, intellectual structure, thematic evolution, and emerging research trends in smart and sustainable manufacturing research within the Industry 4.0 context. A bibliometric analysis was conducted using 616 English-language journal articles indexed in the Scopus database during the 2020– 2025 period. Data were analyzed using Biblioshiny and VOSviewer to evaluate publication trends, country productivity, thematic structures, keyword co-occurrence networks, and topic evolution. The results reveal a substantial increase in research output after 2023, indicating growing global attention toward intelligent and sustainable industrial transformation. China becomes the most productive country, while smart manufacturing, Industry 4.0, and sustainable development were identified as the dominant research themes. The analysis demonstrates strong interconnections among artificial intelligence, machine learning, predictive maintenance, energy efficiency, and sustainable production systems. Emerging topics such as Industry 5.0, green manufacturing, carbon emission reduction, and green economy indicate a transition from automation-oriented manufacturing toward intelligent, human-centric, and environmentally sustainable industrial ecosystems. This study contributes to the literature by providing an updated bibliometric of the convergence between intelligent technologies and sustainability-oriented manufacturing research. The findings offer valuable insights for researchers, industrial practitioners, and policymakers in identifying future research directions and supporting sustainable industrial transformation strategies.